Cell response to mechanical microenvironment cues via Rho signaling: From mechanobiology to mechanomedicine. (15th March 2023) - Xie, Ning; Xiao, Cailan; Shu, Qiuai; Cheng, Bo; Wang, Ziwei; Xue, Runxin; Wen, Zhang; Wang, Jinhai; Shi, Haitao; Fan, Daiming; Liu, Na; Xu, Feng
Abstract: Mechanical cues in the cell microenvironment such as those from extracellular matrix properties, stretching, compression and shear stress, play a critical role in maintaining homeostasis. Upon sensing mechanical stimuli, cells can translate these external forces into intracellular biochemical signals to regulate their cellular behaviors, but the specific mechanisms of mechanotransduction at the molecular level remain elusive. As a subfamily of the Ras superfamily, Rho GTPases have been recognized as key intracellular mechanotransduction mediators that can regulate multiple cell activities such as proliferation, migration and differentiation as well as biological processes such as cytoskeletal dynamics, metabolism, and organ development. However, the upstream mechanosensors for Rho proteins and downstream effectors that respond to Rho signal activation have not been well illustrated. Moreover, Rho-mediated mechanical signals in previous studies are highly context-dependent. In this review, we systematically summarize the types of mechanical cues in the cell microenvironment and provide recent advances on the roles of the Rho-based mechanotransduction in various cell activities, physiological processes and diseases. Comprehensive insights into the mechanical roles of Rho GTPase partners would open a new paradigm of mechanomedicine for a variety of diseases. Statement of significance: In this review, we highlight the critical role of Rho GTPases as signal mediators to respond to physical cues in microenvironment. This article will add a distinct contribution to this set of knowledge by intensively addressing the relationship between Rho signaling and mechanobiology/mechanotransduction/mechanomedcine. This topic has not been discussed by the journal, nor has it yet been developed by the field. The comprehensive picture that will develop, from molecular mechanisms and engineering methods to disease treatment strategies, represents an important and distinct contribution to the field. We hope that this review would help researchers in various fields, especially clinicians, oncologists and bioengineers, who study Rho signal pathway and mechanobiology/mechanotransduction, understand the critical role of Rho GTPase in mechanotransduction. Graphical abstract: Image, graphical abstract